Incidence of infection associated with eculizumab: a meta-analysis of 9 randomized controlled trials - Jiang, Aidou; Liu, Ying; Wei, Chunyan; Xiao, Guirong (Frontiers in Pharmacology, 2025)
Background and AimsEculizumab is expected to lead to increased susceptibility to infection. We performed a meta-analysis of data from randomized controlled trials (RCTs) to determine the risk of infection in eculizumab-treated patients.MethodsWe searched PubMed, EMBASE, Web of Science and ClinicalTrials.gov (up to 8 Oct 2024) to identify published RCTs that focused on the occurrence of infection in patients treated with eculizumab regardless of the indications of the patients. Relative risks and 95% confidence intervals (95% CIs) were calculated via the random effects model. (PROSPERO Code No. CRD42024562470).ResultsNine RCTs including 691 patients were eligible. Compared with the control (placebo or standard of care), eculizumab did not significantly increase the overall risk of infection (RR = 1.07; 95% CI, 0.89–1.28; I2 = 44%), regardless of whether the infection was a general infection (RR = 1.07; 95% CI, 0.86–1.34; I2 = 39%) or a serious infection (RR = 1.05; 95% CI, 0.75–1.47; I2 = 11%). Analyses of subgroups revealed that eculizumab significantly increased the risk of general urinary system infection (RR = 1.33; 95% CI, 1.00–1.77; I2 = 46%) and severe bacteremia (RR = 2.31; 95% CI, 1.04–5.13; I2 = 0%).ConclusionCompared with placebo or standard of care, although eculizumab did not significantly increase the overall risk of infection, it was associated with 33% and 131% increases in the risk of general urinary system infection and severe bacteremia, respectively.Systematic Review registrationPROSPERO CRD42024562470